As frações que o ladrilhamento revela - Ribeiro, Adevanilde Batagin Martins (2013)
This dissertation presents the follow-up of the study of fractions by means of a square lattice, with the variation of molds. The trial is based on interactive work, which provides the cognitive breakthrough of the whole group. Traces a trajectory of the fraction, within the history of mathematics with the evolution to the present day presents some guidelines and methodological indications for teaching fractions. The guiding this research question is: How to identify and deal with the questions that arise during the resolution of situations where students are unable to apply the concepts of fractions, already experienced in their previous school life? In an attempt to resolve the issue of research, was set the goal of research is to provide an intervention that would change for the better the students ' contact with the issues involving the knowledge related to the ideas of ordinary fractions. The research work was Didactic Engineering methodology, was developed in the classroom, through a didactic sequence consisting of two sequences of activities: the Pentaminos game and the Lattice. With this speech, is expected to meet the goal of guiding research and answer the research question.